Factors Affecting Willingness to Pay for Improved Water Supply System in Rural Tanahu, Nepal - Dhungana, Ananta Raj; Baral, Basanta (Janapriya Journal of Interdisciplinary Studies, 2017)
This study aims to analyze the factors associated with willingness to pay for improved water supply system in rural Tanahu, Nepal. For this purpose, one hundred and twenty seven households were proportionately distributed among wards 5, 6, 7 & 8 and selected for data collection. Structured questionnaire was used to collect the data. Chi-square test was used to find the factors associated with willingness to pay for improved water supply system. This study shows that there is no any significant association between willingness to pay for improved water supply system and social, demographic and economic variables. However, water source, dental pain, water quantity, want for change are water fetching time have significant association with willingness to pay for improved water supply system. Cases of Jaundice is significantly associated with willingness to pay for improved water supply system However, there is no significant association between willingness to pay and satisfaction from WUC activities, water purification, diarrhea, dysentery, seasonal flu, and suffering from worm. So, it can be concluded that type of water source, quantity, fetching time, will for change, and prevalence of some disease (Jaundice, Dental Pain) are the major factors influencing willingness to pay for improved water supply system in the study area. apriya Journal of Interdisciplinary Studies, Vol. 5 (December 2016), Page: 1-13